Muzakki's Commitment Improvement Model in Distributing ZIS Funds Through Prosocial Values Behavioral Approach - Murwenie, Ira; Fattah, Nanang; Kusnendi, Kusnendi; Sultan, Mokhamad Adib; Wibowo, Lili Adi (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
The presence of Islamic insurance is an alternative, in order to avoid conventional insurance which is considered to have elements of usury, maytsir, gharar and zholim. In the era of economic disruption, Islamic insurance players and customers are waiting for the direction of strategic policies from the government as regulator and facilitator. The formulation of a sharia insurance development strategy policy begins with analyzing the obstacles to developing sharia insurance in Indonesia. These constraints mean that the number of sharia insurance customers in Indonesia is not maximal. These obstacles include the lack of socialization and promotion, inadequate use of technology, lack of product and service development, lack of knowledge, and the existence of conventional insurance. Based on these constraints, strategies for developing sharia insurance in Indonesia that can be carried out include maximizing socialization and promotion, maximizing the use of technology, developing products and services, increasing literacy, and market penetration. This research is aimed at analyzing the constraints and development strategies of Islamic insurance using a mathematical method, namely the Analytic Network Process (ANP) method, so that policy recommendations are supported by scientific studies. Furthermore, in this study the ANP method was adopted in a survey design involving a number of respondents. The heterogeneity of the assessments of a number of respondents is expected to provide a more rational alternative. The results of the analysis using the ANP method are priority constraints in order to get more attention and priority strategies that can be used to formulate policies to make them more focused.